TREM-1 amplifies trophoblastic inflammation via activating NF-κB pathway during preeclampsia. (November 2021) - Xie, Yin; Li, Xuanxuan; Lv, Dan; He, Mengzhou; Sun, Yanan; Lin, Xingguang; Fan, Yao; Yang, Meitao; Xu, Heze; Zhang, Xiaolei; Zhang, Yanling; Beejadhursing, Rajluxmee; et al.
Abstract: Introduction: Excessive activation of maternal systemic inflammation is one of the underlying causes of pathology during the disease course of preeclampsia (PE). The triggering receptor expressed on myeloid cells-1 (TREM-1) participates in the development and persistence of inflammation. We hypothesized that dysregulated TREM-1 may be involved in the pathogenesis of PE by promoting the secretion of trophoblastic pro-inflammatory cytokines that augment inflammation. Methods: The localization of TREM-1 in placenta and the extravillous trophoblast cell line (TEV-1) was determined by immunohistochemical staining. The expression level of TREM-1 and pro-inflammatory cytokines in placentas were compared between normal pregnancies and PE. We used lipopolysaccharide (LPS) to simulate trophoblastic inflammation. TEV-1 cells were transfected with TREM-1 plasmid and si-TREM-1 respectively, and then were incubated with LPS. The expression levels of pro-inflammatory cytokines and key molecules featured in nuclear transcription factor-kappaB (NF-κB) pathway were detected. Transwell assays were used to detect the effects of TREM-1 on cell migration and invasion. Results: TREM-1 was localized on both villous trophoblasts (VTs) and extravillous trophoblasts (EVTs). TREM-1 and pro-inflammatory cytokines were up-regulated in preeclamptic placenta. Overexpression of TREM-1 promoted the activation of NF-κB pathway and the release of pro-inflammatory factors induced by LPS, and enhanced migration and invasion of TEV-1 cells. Inhibition of TREM-1 significantly attenuated LPS-induced effects and suppressed migration and invasion. Discussion: This study suggested that TREM-1 was up-regulated in PE, and may promote the production of downstream inflammatory factors by activating NF-κB pathway in trophoblastic cells, thus exerting pro-inflammatory effects in the pathogenesis of PE. Highlights: TREM-1 was located on both villous trophoblasts and extravillous trophoblasts. TREM-1 was up-regulated in the placentae of PE. TREM-1 may exert pro-inflammatory effects by activating NF-κB pathway in TEV-1 cells. TREM-1 promoted the migration and invasion of TEV-1 cells.